2019
DOI: 10.1093/mnrasl/slz019
|View full text |Cite
|
Sign up to set email alerts
|

Detection of methoxymethanol as a photochemistry product of condensed methanol

Abstract: We report the identification of methoxymethanol (CH 3 OCH 2 OH) as a photochemistry product of condensed methanol (CH 3 OH) based on temperature-programmed desorption studies conducted following photon irradiation at energies below the ionization threshold (9.8 eV) of condensed methanol. The first detection of methoxymethanol in the interstellar medium was reported in 2017 based on data from Bands 6 and 7 from the Atacama Large Millimeter/submillimeter Array (ALMA). The cosmic synthesis of "complex" organic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Methoxymethanol CH 3 OCH 2 OH was first detected in the ISM in 2017 using the Atacama Large Millimetre/submillimetre Array (ALMA) toward NGC 6334I, a massive protostar (McGuire et al 2017). Experiments made on temperature-programmed desorption studies, have confirmed that CH 3 OCH 2 OH is a photochemistry product of condensed methanol CH 3 OH (Schneider et al 2019). Despite that, previous work using interstellar ices under the influence of ionizing radiation have proposed formation pathways for this key molecule (Zhu et al 2019).…”
Section: Formation Pathways Of Ch 3 Och 2 Ohmentioning
confidence: 99%
“…Methoxymethanol CH 3 OCH 2 OH was first detected in the ISM in 2017 using the Atacama Large Millimetre/submillimetre Array (ALMA) toward NGC 6334I, a massive protostar (McGuire et al 2017). Experiments made on temperature-programmed desorption studies, have confirmed that CH 3 OCH 2 OH is a photochemistry product of condensed methanol CH 3 OH (Schneider et al 2019). Despite that, previous work using interstellar ices under the influence of ionizing radiation have proposed formation pathways for this key molecule (Zhu et al 2019).…”
Section: Formation Pathways Of Ch 3 Och 2 Ohmentioning
confidence: 99%
“…Among them, methanol (CH 3 OH) one of the most abundant COMs in the ISM, is considered as an important radical precursor . There are several studies addressing the radiation-induced chemistry of this molecule in different kinds of astrochemically relevant ices, and under exposure to different radiation sources such as electrons (Bennett et al 2007;Boamah et al 2014;Maity et al 2015), protons (Modica & Palumbo 2010;Occhiogrosso et al 2011), X-rays (Chen et al 2013;Saenko & Feldman 2016), and VUV light (Öberg et al 2009;Henderson & Gudipati 2015;Abou Mrad et al 2016;Paardekooper et al 2016;Schneider et al 2019), simulating different ISM environments. The vast amount of COMs that can be formed from radiation-induced transformations of this single molecule and its mixtures with other zeroth-precursors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The current work also shows that CH 2 OH + is an intermediate in the formation routes of COMs such as methoxymethanol CH 3 OCH 2 OH (Schneider et al 2019). The formation pathway of methoxymethanol has been proposed as the recombination of the methoxy and hydroxymethyl radicals (McGuire et al 2017).…”
Section: Hydroxymethyl Cation Ch 2 Oh +mentioning
confidence: 56%